2017
DOI: 10.3122/jabfm.2017.02.160264
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Suicide Ideation and Attempt Among Substance-Using Patients in Primary Care

Abstract: Background Suicide is a major public health concern, particularly among people who use illicit substances and/or non-prescribed medications. Objective The present study prospectively assessed the incidence and predictors of suicidal ideation (SI) and suicide attempt (SA) among such substance-using patients over 12 months after receiving primary care. Design Secondary analysis of data from a randomized clinical trial of screening, brief intervention, and referral to treatment for substance use within seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
1
24
0
3
Order By: Relevance
“…In America, the study revealed that suicidality was elevated in patients who reported depression or anxiety (AOR = 1.10, P = 0.03), and violent behavior (AOR = 2.59, P < 0.001) [4]. A similar study was done in USA revealed that anxiety is a predictor of suicide ideation (AOR = 1.49, 95% CI 1.18-1.88, P < 0.01).…”
Section: Introductionmentioning
confidence: 69%
“…In America, the study revealed that suicidality was elevated in patients who reported depression or anxiety (AOR = 1.10, P = 0.03), and violent behavior (AOR = 2.59, P < 0.001) [4]. A similar study was done in USA revealed that anxiety is a predictor of suicide ideation (AOR = 1.49, 95% CI 1.18-1.88, P < 0.01).…”
Section: Introductionmentioning
confidence: 69%
“…These findings are similar to those found in another study which predicted that risk for subsequent attempts is higher among those with recent suicidal ideation and previous suicide attempts. 35 History of smoking was positive in greater number of participants in the group, which used alcohol to facilitate the suicidal attempt. This finding concurs to previous study showing cigarette smoking is associated with higher rates of suicide.…”
Section: Discussionmentioning
confidence: 94%
“…In the general population, major depression increases the risk of patients to suffer from comorbid cocaine dependence by more than twice . In turn, this comorbidity reduces the chances of abstinence, and perhaps increase the risk of relapse to drug use .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated a strong association between cocaine dependence and depression, yielding higher risk of suicide and greater social and personal impairment, with each disorder being complicated by the other . One of the leading hypotheses regarding this comorbidity postulates that depressed patients tend to consume drugs in an attempt to “self‐medicate”; however, the experimentally controlled evidence for this hypothesis is limited and animal models that can validate and evaluate the relation between depression and addiction or contribute to the understanding of the neurobiological mechanism, are lacking.…”
Section: Introductionmentioning
confidence: 99%